Os álbuns fotojornalísticos online e a construção do acontecimento: atribuições de sentido a partir da composição imagética dos protestos de junho - Casadei, Eliza Bachega [UNESP] (2014)
Given that the choices involved in the selection of compositional techniques in photography are mediated by values, this article aims to analyze the compositional techniques of photographs published by photojournalistic online albums during the protests of June 2013 in Brazil. These albums feature professional and amateur photographs considered "the best" of this event and, interestingly, the chosen photographs have several composition techniques in common. We will examine these images from the perspective of significant effects that these techniques engender with the objective of examining the meanings that were attributed to that event in those albums.